2010
DOI: 10.1002/cmdc.201000276
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiplasmodial Activity of Highly Active Reverse Analogues of the Antimalarial Drug Candidate Fosmidomycin

Abstract: Delving into digallides: The characteristics of the chemical bonding of the digallides of the alkaline‐earth metals (see figure) have been studied by application of experimental methods, such as single‐crystal X‐ray diffraction and solid‐state NMR spectroscopy, in combination with quantum mechanical calculations. Combined application of 69,71Ga NMR spectroscopy and quantum mechanical calculations reveals the chemical bonding in the digallides of Ca, Sr, and Ba. An analysis of the electron localization functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 74 publications
1
39
1
Order By: Relevance
“…Additional structural variations around the phosphonate anchor and the spacer of this compound gave new whose structures are given in Fig. 8 and IC 50 are presented in Table 3 [56, 57]. Indeed, a new highly active and selective pf -DXR inhibitor with a unique chemical structure (compound 28 ) was developed by Behrendt et al .…”
Section: The Mep Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Additional structural variations around the phosphonate anchor and the spacer of this compound gave new whose structures are given in Fig. 8 and IC 50 are presented in Table 3 [56, 57]. Indeed, a new highly active and selective pf -DXR inhibitor with a unique chemical structure (compound 28 ) was developed by Behrendt et al .…”
Section: The Mep Pathwaymentioning
confidence: 99%
“…Indeed, a new highly active and selective pf -DXR inhibitor with a unique chemical structure (compound 28 ) was developed by Behrendt et al . [57]. Molecule 28 is an α-phenyl phosphonic acid derivative of 17 .…”
Section: The Mep Pathwaymentioning
confidence: 99%
“…Interestingly, both FSM and FR900098 inhibited BaDRL with less efficiency than EcDXR (Fig. 5A), resulting in IC 50 values for BaDRL that were ϳ10-fold higher than those reported in the literature for DXR (39,41). This might be due to the structural differences between the two types of enzymes since the large size of the pocket around the hydroxamic acid tail of both FSM and FR900098 in BaDRL is predicted to result in looser binding compared with DXR enzymes (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…1) are excellent DXR inhibitors that consistently fit well into the active site of EcDXR (supplemental Fig. S4C) (39,40). However, positioning of compounds 3 and 4 into the BaDRL structure revealed that, for the two possible stereoisomers of both compounds, the ␣-phenyl group would either crash against the side chain of Phe-223 (supplemental Fig.…”
Section: Resultsmentioning
confidence: 95%
“…16, 17 At the other end of the molecule, reversal of the hydroxamate moiety has also been shown to improve antimalarial properties, particularly in tandem with the aforementioned efforts. 18 …”
mentioning
confidence: 99%